Laser Techniques and Laser Physics in Polish Laboratories - Abramski, Krzysztof M. (Photonics Letters of Poland, 2014)
<!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> This issue of Photonics Letters of Poland is the continuation of the overview of Polish research groups working on lasers, their physics and technologies. It contains 16 papers. This set of papers gives the rough scan of research groups in Poland, which are more or less engaged into research and development of lasers.